2023
DOI: 10.3390/app13095363
|View full text |Cite
|
Sign up to set email alerts
|

Pareto-Optimized AVQI Assessment of Dysphonia: A Clinical Trial Using Various Smartphones

Abstract: Multiparametric indices offer a more comprehensive approach to voice quality assessment by taking into account multiple acoustic parameters. Artificial intelligence technology can be utilized in healthcare to evaluate data and optimize decision-making processes. Mobile devices provide new opportunities for remote speech monitoring, allowing the use of basic mobile devices as screening tools for the early identification and treatment of voice disorders. However, it is necessary to demonstrate equivalence betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The high performance of smartphone microphones has been further proven in studies showing how they outperform standard external microphones in recording and analyzing normal and dysphonic voices [ 7 ]. Lastly, it was demonstrated that smartphones are useful in restoring pathological voices and allowing greater access to voice therapy for patients with dysphonia [ 8 ]. It should be noted, though, that challenges such as device limitations in continuous voice tracking have been identified, highlighting the need for further technological advancements to overcome these barriers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high performance of smartphone microphones has been further proven in studies showing how they outperform standard external microphones in recording and analyzing normal and dysphonic voices [ 7 ]. Lastly, it was demonstrated that smartphones are useful in restoring pathological voices and allowing greater access to voice therapy for patients with dysphonia [ 8 ]. It should be noted, though, that challenges such as device limitations in continuous voice tracking have been identified, highlighting the need for further technological advancements to overcome these barriers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%